Machado de Assis: cinismo e realismo - Santos, Marcelo Burmann dos (2019)
The present thesis analyzed the problem of cynicism and realism in the work of Machado de Assis (1839-1908). It is known that Machado is the pantheon of the canons of national literatures, perhaps international ones. Not surprisingly, revisiting the work of our great realist was an arduous task, since everything has apparently been said about it: from the daily newspapers critiques, through the meanderings of specialized critiques - biographical, formalist, sociological, and so on. - it is easy to see the prestige that Machado's work still has in the contemporary world. Therefore, without ever giving up these critical essays, the problem we undertook in this research was postulated while reviewing Machado once more: the relation between the development of capitalist productive forces in the colony, the peculiarity of Brazilian capitalism, and how Brazilian colonial and semi-colonial practices of the eight hundred are conformed in the work of our author. For this, Peter Sloterdijk's Critical of Cynical Reason (2012), which illuminated us in the understanding of cynicism as a way of conceiving inter- and intra-class relationships in effective capitalist modernity, was used as an initial theoretical input (ECHEVERRÍA, 2011), without giving up, however, the cynical element of antiquity, that is, insolence or plebeian laughter, a device capable of disturbing the conduct of serious or conformists. The Marxist aesthetic studies of Györg Lukács during his more than forty years of reflection and bibliographical production about unfolding and configurations of the constantly changing reality of fiction, with emphasis on narratives, are also essential for this research. That is, the problem of realism with reality. Another study for which we have great debt are the investigations of Roberto Schwarz, especially in A master on the periphery of capitalism (2000b), who has brought us the light to investigate the problems of the Machado novel that we list for analytical purposes, Posthumous Memoirs of Brás Cubas (1881), and the peculiarity of nineteenth-century Brazilian capitalism. Thus, within the limits of the research provided by a short academic master's degree, we try simply to contribute to the critical essays of one of the most extraordinary writers in Brazilian literature.